Recovery of the N-15-labelled fertiliser in citrus trees in relation with timing of application and irrigation system - Quinones, Ana; Banuls, Josefina; Primo-Millo, Eduardo; Legaz, Francisco (2017)
Citrus trees demand high amounts of nitrogenous fertilisers as N has a greater influence on growth and production than other nutrients (Smith, 1966). Citrus farmers have applied high dosages of N because of slight enhances in fruit yield with increasing N applications and poor fertilising criteria. This has resulted in a deterioration in the commercial quality of the fruit (Chapman, 1968), a reduction in the profitability of the citrus crops (Wild, 1992) and an alarming increase in the concentration of the nitrate ion in groundwaters (Bingham et al., 1971; Fernández et al., 1998; Burkart and Stoner, 2002). We have used information on the annual N requirements established for citrus trees to recommend the optimum N dose in the Valencian region (Legaz and Primo-Millo, 1988a). These N requirements may be adjusted according to the N uptake efficiency of fertilisers. The use of fertilisers enriched with 15N can provides knowledge about the fate of the N applied in the plant-soil-water system (Wallace et al., 1954; Akao et al., 1978; Feingenbaum et al., 1987; Legaz and Primo-Millo, 1988b; Martínez et al., 2002).